(untitled) (Hematology Meeting Reports, 2009)
Treatment of Multiple Myeloma (MM) has significantly changed over the last few years. In young patients the use of novel schemes based on Thalidomide, Lenalidomide, or, Bortezomib appear to be superior to VAD as debulky pre-transplant regimens and these schemes do not affect stem cell collection, although some precautions should be taken with Lenalidomide. Interestingly, the initial CR rate obtained with these combinations (particularly with Bortezomib, as shown in two randomized trials) was upgraded following ASCT, which suggests that these novel treatments will not replace ASCT, but will help to enhance its activity, although the EFS and OS of this approach is still unknown. Regarding the role of novel drugs in maintenance therapy after transplant, two randomized trials have shown that Thalidomide maintenance prolongs EFS and OS, particularly in those patients who fail to achieve CR after Transplant. Nevertheless, prolonged treatment may be associated with more resistant relapses to salvage therapy.